2014
DOI: 10.4238/2014.february.21.11
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of neutrophil gelatinase-associated lipocalin (NGAL) in colorectal cancer: a meta-analysis

Abstract: ABSTRACT. Growing evidence has implicated that neutrophil gelatinase-associated lipocalin (NGAL) plays a role in a spectrum of human cancers. Several observational studies from different parts of the world have been devoted to elucidate the clinical relationship between NGAL and colorectal cancer. This meta-analysis aimed to explore the overall accuracy of NGAL detection for the diagnosis and prognosis of colorectal cancer. Based on comprehensive literature screening on Pubmed, Ovid, and CNKI databases, our sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Recent studies have found that serum and urine LCN2 concentrations may have diagnostic and prognostic utility in colorectal, pancreatic, and thyroid cancer. 20,43,44 Future studies using patient serum samples will be important to assess LCN2 expression and whether LCN2 can be used in conjunction with a-fetoprotein to aid in the diagnosis, surveillance, prognosis, and even therapeutic response of HB. Serum and urine LCN2 levels are also elevated in a variety of liver diseases, mirroring the progression of inflammatory and oxidative damage to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that serum and urine LCN2 concentrations may have diagnostic and prognostic utility in colorectal, pancreatic, and thyroid cancer. 20,43,44 Future studies using patient serum samples will be important to assess LCN2 expression and whether LCN2 can be used in conjunction with a-fetoprotein to aid in the diagnosis, surveillance, prognosis, and even therapeutic response of HB. Serum and urine LCN2 levels are also elevated in a variety of liver diseases, mirroring the progression of inflammatory and oxidative damage to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…NGAL has been found to be up-regulated in some types of cancer and to be down-regulated in others; thanks to the possibility of being detected both in blood and in urine, researchers have started focusing on NGAL as a novel noninvasive biomarker for cancer. Two previous systematic reviews (53,54) explored the overall accuracy of NGAL detection for the diagnosis and prognosis of breast and colorectal cancers. The authors reported a relationship between the up-regulation of NGAL and both types of cancer, suggesting NGAL as a potential diagnostic and prognostic biomarker, nevertheless its role needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…LCN2 encodes lipocalin 2 or neutrophil gelatinase associated lipocalin ( NGAL ), a secreted 25-kDa protein that binds iron [ 25 ] and is overexpressed in various epithelial cancers [ 26 ]. Several findings indicate that LCN2 overexpression is associated with tumor size, stage, and invasiveness [ 27 ], and it has been proposed as a negative prognostic indicator in several types of cancer [ 28 , 29 ]. We found that LCN2 mRNA levels were markedly higher in PTCs than in NTs, and immunostaining for LCN2 protein was positive in several tumors but in none of the NT samples.…”
Section: Discussionmentioning
confidence: 99%